Self Control Regulation And Blood Pressure On Hypertension Patient - Diana Rachmania; Dhina Widayati; Madiha Mukhtar (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Hypertension causes sufferers to have to live a healthy lifestyle so that blood pressure remains well controlled. Self-control regulation in hypertension sufferers determines how to behave in a healthy lifestyle in order to maintain blood pressure at normal conditions. The purpose of this study is to determine the relationship between self control regulation and blood pressure in hypertensive patients. Correlation study with a cross-sectional approach was the design in this study. The population of hypertension sufferers were 76. Samples were taken through purposive sampling technique and obtained a total of 64 respondents. Self-control regulation as the independent variable was measured with an instrument in the form of a questionnaire and blood pressure as the dependent variable was measured with an observation sheet. Data were analyzed by Spearman's rho test with the condition that H1 was accepted if the p value <α (0.05). The results showed that half of the respondents (50%) had high self-control and almost half of the respondents (44%) had blood pressure in the pre-hypertension criteria. Analysis of Spearman's rank test data p-value 0.006 <0.05 shows that there was a relationship between self-control regulation and blood pressure in hypertensive patients with a strong relationship (r = 0.860) with a positive relationship. This means that the higher the self-control regulation, the hypertensive patient is able to maintain blood pressure conditions close to normal. It is recommended that people with hypertension maintain good self-control abilities so that blood pressure can be controlled properly.